Simultaneous determination of Cu(II), Zn(II), and Pb(II) from aqueous solutions using a polymer inclusion membrane (PIM) based-sensor with 1-(2-pyridylazo)-2-naphthol (PAN) as chromophore and chemometric methods - Mancilla-Rico, Alejandro J.; Rodríguez de San Miguel, Eduardo (Frontiers in Analytical Science, 2022)
Polymer inclusion membranes (PIMs) are developed to be used as colorimetric sensors for the simultaneous determination and quantification of Cu(II), Zn(II), Pb(II) from aqueous solutions using chemometric methods. Different physical and chemical factors that influence the detection process of the analytes are studied, i.e., the concentration of the metal cation, the amount of membrane, and the pH of the solution. The most significant variables within the detection process in membrane sensors are those that are closely related to the chemical reaction of the detection, that is, the concentration of the metal cation and the number of active sites available in the optomembrane. The reversibility and durability of the signal are evaluated as well. The optomembrane reaches 95% of the optical signal attributed to the process of formation of the different colorful complexes in 20 min, regardless of the metal cation. The optomembrane of CTA—TEHP—PAN presents a very narrow linear interval of response to the concentration of the cations, Zn(II) and Cu(II) ranging from 0.6 to 6 ppm; for higher concentrations the polymeric detector presents saturation. The response of the sensor to different concentrations of Pb(II) is not linear, which can be attributed to the lack of chemical affinity to generate the complex in the polymer film. The simultaneous determination of the three metal cations by three chemometric methods [multivariate curve resolution (MCR), artificial neural networks (ANNs) and partial least squares (PLS)] is performed with an experimental central composite design matrix at five levels and three experimental factors. The construction of the quantification model is carried out from the information obtained from the VIS spectrum of the PIMs exposed to the aqueous solutions. The predictive power of the quantification models for each of the metal cations is evaluated contemplating the determination coefficient (R2) and the root mean square error (RMSE) values. Results favors the use of the PLS algorithm, although due to the competition for the actives sites of the chromophore, Pb(II) determination is not satisfactorily acomplished. Principal component analysis (PCA) is in addition employed to visualize patterns in the synthesized membranes.